Ռուբէն Սեւակի ստեղծագործութիւնը՝ Վլադիմիր Կիրակոսեանի մեկնութեամբ - Սարգսյան, Նառա (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Рассматривается научная работа В. Киракосяна «Рубен Севак (жизнь и творчество)», посвященная жизни и творчеству западноармянского поэта Р. Севака, как литературное открытие того времени, Показано, что литературовед В. Киракосян, на основе тщательного анализа всего творчества Р. Севака, затрагивает важные вопросы, которые остались вне поля зрения предшествующих исследователей; как целостная картина литературной среды того времени, роль поэта на литературное направление, и ряд․ The article examines the literary critic V. Kirakosyan’s research work entitled as “Ruben Sevak (life and work)” dedicated to the life and work of the Western Armenian poet R. Sevak, as a revelation of the time. It is shown that on the basis of a thorough analysis of R. Sevak’s entire creativity, V. Kirakosyan revealed essential issues that were left out of the view of the previous researchers, like a complete picture of the literary environment of the time, the place of the poet in the unified course of the literary movement and a number of aesthetic-worldview questions. It is noteworthy to mention that V. Kirakosyan places Ruben Sevak among the great Western Armenian poets like Siamanto, M. Metsarents, D. Varujan.
Keywords: Գրախօսութիւն